IMPOSITION OF CRIMINAL LAW IN THE ITE LAW AGAINST DEFAMATION THROUGH FACEBOOK SOCIAL MEDIA - Doris Rahmat; Santoso Budi Nursal Umar (Universitas Negeri Medan, 2024)
Defamation on social media, especially via the Facebook platform, has become an increasingly disturbing issue in society. This research aims to understand theeffectiveness of criminal law enforcement under the Information and Electronic Transactions Law (UU ITE) in cases of defamation on Facebook. Mixedqualitative and quantitative research methods were used, including literature studies, interviews, social media content analysis, surveys, and statistical analysis. The research results show that the phenomenon of defamation on Facebook faces challenges in law enforcement, including difficulties in identifying perpetrators, the length of the legal process, and public distrust of the effectiveness of law enforcement. Recommendations are given to increase cooperation between the police, legal institutions and social media platforms, as well as to increase public education about the dangers of defamation. In conclusion, criminallaw enforcement against defamation on Facebook requires a holistic approach involving various parties and ongoing efforts to create a safer and more ethicaldigital environment. Even though the Information and Electronic Transactions Law (UU ITE) provides a clear legal basis, law enforcement still faces variouschallenges, including difficulties in identifying perpetrators, the length of the legal process, and low public trust in the effectiveness of law enforcement. The proposed recommendations include increasing cooperation between the police, legal institutions and social media platforms, as well as intensifying publiceducation about the dangers of defamation. These steps are important for creating a safer and more ethical digital environment for all users. By understanding the challenges faced and through joint efforts across sectors, it is hoped that criminal law enforcement against defamation on Facebook and social media can beimproved, so that individual human rights can be better protected and the integrity of the digital environment can be maintained.